THE IMPACT OF CELEBRITY ENDORSEMENT ON BRAND IMAGE - Lomboan, Syutria (Universitas Sam Ratulangi, 2013)
ABSTRACT To introduce a product to the public company should provide information about the product that will be introduced to the public and the information must be trusted information and can attract the public attention. To introduce a product to the public at this time requires a lot of means and facilities. One of the examples is advertising. Ads become one of the most instruments used widely by the company to promote a product. In order to support an ad in providing information and attract the attention of the public, a company will use endorser. Research objectives are to analyze the influence of celebrity endorser and the variable to brand image. Theories supporting this research are consumer behaviour, celebrity endorser, and brand image. The population observed in this current research is people that watch the advertising with sample as many as 50 customers or respondents. Results and conclusions are that all variables of celebrity endorser (credibility, attractiveness, expertise, trustworthiness, and celebrity match-up product) influence brand image with credibility is the most influencing variable. Keywords: celebrity endorser, brand image